TAFSSA stakeholder mapping: the agricultural production systems in Bangladesh - Nur A Mahajabin Khan; Amitaksha Nag; Kamal, Mustafa; Nandi, Ravi; Gathala, Mahesh Kumar; Krupnik, Timothy J. (TAFSSA, 2024)
The network mapping workshop aimed to analyze the agricultural production systems in Bangladesh, focusing on crops, livestock, and aquaculture. The workshop explored the roles and interactions of key stakeholders, including government bodies, NGOs, the private sector, academic institutions, research organizations, and international organizations, in shaping the agricultural landscape. The primary research question guiding this effort was: Who are the main organizations and actors influencing agricultural production systems in Bangladesh? Through this analysis, we aimed to uncover key drivers, barriers, and gaps within the system to guide interventions for enhancing the sustainability and effectiveness of the agrifood systems in Bangladesh.